The Implementasi Corporate Sponsorship Catur - Prakarsa, Hamdi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The Corporate Social Responsibility program is not only an activity to get the maximum benefit for capital owners or shareholders, but also provides benefits to the surrounding community. The purpose of this study is to identify and explain the process of a company in designing a chess sponsorship program. In addition, this study aims to find out and explain the sponsorship cooperation framework between PT Japfa Comfeed Indonesia Tbk and PB Percasi and analyze the benefits. This research was conducted using qualitative research with case studies. Data were collected through interviews and literature studies and then reduced by means of abstraction, including to make a summary of the core, process, and statements that must be in it. Based on this research, it can be concluded: 1) In its implementation, the process of social responsibility activities that PT Japfa Comfeed Indonesia Tbk has been in accordance with the company's vision and mission; 2) PT Japfa Comfeed Indonesia Tbk chose chess as a sponsorship-based CSR program because chess is a corporate social investment; 3) In carrying out its social responsibility activities, the scheme carried out by PT Japfa Comfeed Indonesia Tbk is based on the company wanting to gain a benefit from what has been done; 4) The social responsibility activities that PT Japfa Comfeed Indonesia Tbk carry out have an impact, namely the increasingly empowered Indonesian chess athletes due to the consistency of funding carried out. Abstrak Program Corporate Social Responsibility tidak hanya merupakan kegiatan untuk mendapatkan keuntungan sebesar-besarnya bagi pemilik modal atau pemegang saham, melainkan juga memberikan manfaat pada komunitas sekitar. Tujuan dari penelitian ini adalah untuk mengetahui dan menjelaskan proses suatu perusahaan dalam merancang program sponsorship olahraga catur dan menjelaskan seperti apa kerangka kerja sama sponsorship antara PT Japfa Comfeed Indonesia Tbk dengan PB Percasi. Penelitian ini dilakukan menggunakan penelitian kualitatif dengan sifat studi kasus. Data dikumpulkan melalui wawancara dan studi kepustakaan. Berdasarkan penelitian ini dapat disimpulkan: 1) Dalam pelaksanaannya, proses kegiatan tanggung jawab sosial yang PT Japfa Comfeed Indonesia Tbk sudah sesuai dengan visi-misi perusahaan; 2) PT Japfa Comfeed Indonesia Tbk memilih catur sebagai program CSR berbasis sponsorship dikarenakan catur merupakan investasi sosial perusahaan; 3) Dalam pelaksanan kegiatan tanggung jawab sosialnya, skema yang dilakukan PT Japfa Comfeed Indonesia Tbk didasarkan pada perusahaan ingin meraih suatu manfaat dari apa yang telah dilakukan; 4) Kegiatan tanggung jawab sosial yang PT Japfa Comfeed Indonesia Tbk lakukan menimbulkan dampak yaitu semakin terberdayanya atlit catur Indonesia akibat konsistensi pendanaan yang dilakukan.